SRS and Design Analysis: Kunci Kesuksesan Proyek Sistem Informasi yang Efektif - Fadhlirrahman Baso; Aprilianti Nirmala S.; Ibrahim Alkhalil; Dian Arishandy Imansyah (Indonesian Technology and Education Journal, 2024)
The formulation of Software Requirements Specification (SRS) and design analysis are key factors in the success of information system projects. A proper SRS lays a solid foundation for system development, while comprehensive design analysis helps identify system requirements clearly. However, crafting effective SRS and conducting thorough design analysis often pose challenges. This article aims to delineate the roles of SRS and design analysis in the early stages of system development and provide insights into best practices for addressing associated challenges. The methodology involves direct engagement with stakeholders and end-users to deeply understand user requirements. Subsequently, comprehensive requirement analysis and system design analysis are conducted. With the right approach, organizations can enhance the likelihood of success in information system projects, ensuring that the resulting systems meet user needs effectively.